RITUAL SEBAGAI MEDIA TRANSMISI KREATIVITAS SENI DI LERENG GUNUNG MERBABU - Rr. Paramitha Dyah Fitriasari (Jurnal Kawistara, 2012)
Tradition developed in a community should continue to be preserved from generations to generations.Efforts are being made one of which is the process of transmission or inheritance. Transmission can bedone in various ways, one of which is ritual. Rituals which are performed continuously and regularlycan be a good medium for the transmission process. The ritual process of artistic creativity that wasdeveloped by the community on the slopes of Mount Merbabu is an example. Art goes hand in handwith the ritual is one of the transmission mediums used to continue an existing tradition. This researchseeks to show how ritual can be a transmission medium of art, particularly on the slopes of Merbabu.